2009 International Joint Conference on Neural Networks 2009
DOI: 10.1109/ijcnn.2009.5178987
|View full text |Cite
|
Sign up to set email alerts
|

Time perception in shaping cognitive neurodynamics of artificial agents

Abstract: Recent research in cognitive systems aims to uncover important aspects of biological cognitive processes and additionally formulate design principles for implementing artificially intelligent systems. Despite the increasing amount of research efforts addressing cognitive phenomena, the issue of time perception and how it is linked to other cognitive processes remains largely unexplored.In the current paper, we make a first attempt for studying artificial time perception by means of simulated robotic experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The selected time step is sufficiently small to support the interaction of the robot with the environment and additionally it is sufficiently large to reduce the computational resources required to design an artificial brain to the order of approximately one day (when running on a single computer). Similar time steps are typical for robotic simulation experiments, and have been used extensively in our previous studies on time perception (Maniadakis & Trahanias, 2012;Maniadakis et al, 2009aManiadakis et al, , 2009b. Interestingly, the duration of 100 ms is frequently assumed to correspond to the resolution of cognitive steps in our brain (Dehaene & Naccache, 2001;van de Par & Kohlrausch, 2000).…”
Section: Methodsmentioning
confidence: 90%
“…The selected time step is sufficiently small to support the interaction of the robot with the environment and additionally it is sufficiently large to reduce the computational resources required to design an artificial brain to the order of approximately one day (when running on a single computer). Similar time steps are typical for robotic simulation experiments, and have been used extensively in our previous studies on time perception (Maniadakis & Trahanias, 2012;Maniadakis et al, 2009aManiadakis et al, , 2009b. Interestingly, the duration of 100 ms is frequently assumed to correspond to the resolution of cognitive steps in our brain (Dehaene & Naccache, 2001;van de Par & Kohlrausch, 2000).…”
Section: Methodsmentioning
confidence: 90%
“…Our recent works have investigated the role of environmental temporal constraints in shaping cognitive mechanisms (Maniadakis et al, 2009a , b ). It has been shown that system dynamics tend to self-organize mechanisms that consider and exploit time, in order to support the development of high-level cognitive skills (in particular, executive control, in the studies pursued).…”
Section: Implementing Artificial Temporal Cognitionmentioning
confidence: 99%